AuNx stabilization with interstitial nitrogen atoms: A Density Functional Theory Study (2017)
Researchers have been studying 4d and 5d Series Transition Metal Nitrides lately as a result of the experimental production of AuN, PtN, CuN. In this paper, we used the Density Functional Theory (DFT) implementing a pseudopotential plane-wave method to study the incorporation of nitrogen atoms in the face-centered cube (fcc) lattice of gold (Au). First, we took the fcc structure of gold, and gradually located the nitrogen atoms in tetrahedral (TH) and octahedral (OH) interstitial sites. AuN stabilized in: 2OH (30%), 4OH and 4TH (50%), 4OH - 2TH (close to the wurtzite structure) and 6TH (60%). This leads us to think that AuN behaves like a Transition Metal Nitride since the nitrogen atoms look for tetrahedral sites. © Published under licence by IOP Publishing Ltd.